2007
DOI: 10.1007/s11090-007-9082-2
|View full text |Cite
|
Sign up to set email alerts
|

Reforming of CO2-Containing Natural Gas Using an AC Gliding Arc System: Effect of Gas Components in Natural Gas

Abstract: The objective of the present work was to study the reforming of simulated natural gas via the nonthermal plasma process with the focus on the production of hydrogen and higher hydrocarbons. The reforming of simulated natural gas was conducted in an alternating current (AC) gliding arc reactor under ambient conditions. The feed composition of the simulated natural gas contained a CH 4 :C 2 H 6 :C 3 H 8 :CO 2 molar ratio of 70:5:5:20. To investigate the effects of all gaseous hydrocarbons and CO 2 present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
4
31
1
Order By: Relevance
“…Several reports have revealed that the addition of oxygen to a CH 4 -CO 2 feed gas mixture is one of the possible solutions for minimizing both the carbon formation and energy consumption for the CO 2 reforming reaction of methane [29][30][31][32][33]. Hence, in this present study, as the continuation of our previous work [28], the plasma reforming of CO 2 -containing natural gas coupled with partial oxidation was investigated using gliding arc discharge at different voltages, frequencies, and hydrocarbons (HCs)-tooxygen feed molar ratios. A comparative study between adding pure oxygen and adding air in the feed stream for the reforming of natural gas under gliding arc discharge was also conducted.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…Several reports have revealed that the addition of oxygen to a CH 4 -CO 2 feed gas mixture is one of the possible solutions for minimizing both the carbon formation and energy consumption for the CO 2 reforming reaction of methane [29][30][31][32][33]. Hence, in this present study, as the continuation of our previous work [28], the plasma reforming of CO 2 -containing natural gas coupled with partial oxidation was investigated using gliding arc discharge at different voltages, frequencies, and hydrocarbons (HCs)-tooxygen feed molar ratios. A comparative study between adding pure oxygen and adding air in the feed stream for the reforming of natural gas under gliding arc discharge was also conducted.…”
Section: Introductionmentioning
confidence: 51%
“…1. The details of the gliding arc reactor configuration and the discharge system were described in the previous paper [28]. The gliding arc reactor is made of a glass tube with a 9 cm OD and an 8.5 cm ID, and has two diverging knife-shaped electrodes that were fabricated from stainless steel sheets with a 1.2 cm width for each electrode.…”
Section: Ac Gliding Arc Discharge Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Generally, gliding arc discharge showed lower energy cost (EC) than corona discharge, microwave discharge, or DBD. 16 However, the conversions of CO 2 and CH 4 in gliding arc discharges are relatively low.…”
Section: Introductionmentioning
confidence: 99%